Impact of Dose Titration Using the Seizure Quality Rating (SQR) Scale on Electroconvulsive Therapy (ECT) Outcomes: A Quality Improvement Project - Mohsin Nazeer Muhammed; Raja Badrakalimuthu (BJPsych Open)
Aims: This Quality Improvement Project (QIP) aimed to assess the impact of incorporating the Seizure Quality Rating (SQR) scale into ECT dose titration practices. The objective was to optimize treatment by improving seizure quality assessment and reducing cognitive side effects associated with higher electric doses, ultimately enhancing patient outcomes.